Tinjauan Yuridis terhadap Kewenangan Pengadilan Negeri Jakarta Pusat terkait Penundaan Pemilu 2024 dan Implikasi Keberlakuan Asas Erga Omnes - Arimbi, Diah; Amanita, Aliesa; Andayani, Lily; Dwiprigitaningtias, Indah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The postponement of the General Election (Pemilu) is a crucial issue in a democratic state governed by law such as Indonesia, where the constitution mandates elections be held every 5 (five) years. Controversy arose from the Central Jakarta District Court Decision Number 757/Pdt.G/2022/PN Jkt Pst, which ordered the General Election Commission (KPU) to postpone the 2024 General Election. This decision not only contradicted the constitution but was also problematic for ruling beyond the plaintiff's demands (ultra petitum partium). The indication of applying the principle of erga omnes in the decision also became a separate polemic, considering that this principle is fundamentally relevant only in the realm of public law, whereas the Central Jakarta District Court operates within the scope of private law. This research employs a normative juridical approach with descriptive-analytical specification, and a normative qualitative analysis method by analyzing Decision Number 757/Pdt.G/PN Jkt Pst against positive law provisions in Indonesia. The conclusion of the study indicates that Central Jakarta District Court Decision Number 757/Pdt.G/PN Jkt Pst is an invalid decision, as the Panel of Judges exceeded its authority (ultra vires) and ruled ultra petitum partium. Furthermore, the principle of erga omnes cannot be applied to the decision because it is inherently applicable only to court decisions within the scope of public law, not private law.